Early modern diplomacy and French festival culture in a European context, 1572-1615 - Leuveren, Bram van (Rulers & elites, 2023)
"This book is the first to explore the rich festival culture of late sixteenth- and early seventeenth-century France as a tool for diplomacy. Bram van Leuveren examines how the late Valois and early Bourbon rulers of the kingdom made conscious use of festivals to advance their diplomatic interests in a war-torn Europe and how diplomatic stakeholders from across the continent participated in and responded to the theatrical and ceremonial events that featured at these festivals. Analysing a large body of multi-lingual eyewitness and commemorative accounts, as well as visual and material objects, Van Leuveren argues that French festival culture operated as a contested site where the diplomatic concerns of stakeholders from various national, religious, and social backgrounds fought for recognition"--